Why do the poor pay more? Exploring the poverty penalty concept - Mendoza, Ronald U (Archīum Ateneo, 2011)
The poverty penalty refers to the relatively higher cost shouldered by the poor, when compared to the non‐poor, in their participation in certain markets. By trying to further develop this concept, this paper clarifies some of the subtle and more direct ways through which the poor could be marginalised in the market system. A brief review of the business and economics literature suggests that there are different possible causes behind various forms of the poverty penalty, and hence distinct ways to address them, depending on its form, the nature of the market under analysis, the specific country context, the characteristics of the poor themselves and the prevalence of market failures among other factors. Copyright © 2008 John Wiley & Sons, Ltd.